(untitled) (International Journal of Biomedical Research, 2014)
Introduction: Sweepers are exposed to the dust generated during sweeping activity. Inhalation of dust and airborne particulates irritate the respiratory tract leading to respiratory diseases. Objectives: This study was undertaken to find out the prevalence of work related respiratory and non respiratory symptoms in female sweepers Methods: The study was done in 30 female sweepers and 30 healthy female control subjects. All the subjects were matched for age, height and weight. A modified British Medical Research Council Questionnaire on Respiratory Symptoms was used in the studyand information regarding non respiratory symptoms were also obtained. Statistical analysis done using Studentst test and Chi square test. Results : The prevalence of respiratory symptoms in sweepers were nose irritation (50%), sneezing (46.6), Rhinitis (40%), cough (36.6 %), phlegm (26.6%), Wheezing (23%) .The commonest non respiratory symptom was back pain (70%) Conclusions: Based on the results of the present study it may be concluded occupational exposures to dust among sweepers and sweeping without precautionary measures may predispose to respiratory and non-respiratory symptoms.. We recommend that the workers should use protective face mask, do wet sweeping instead of dry sweeping during work and use of long handled brooms.